2009
DOI: 10.1073/pnas.0806638106
|View full text |Cite|
|
Sign up to set email alerts
|

Demographic models and IPCC climate projections predict the decline of an emperor penguin population

Abstract: Studies have reported important effects of recent climate change on Antarctic species, but there has been to our knowledge no attempt to explicitly link those results to forecasted population responses to climate change. Antarctic sea ice extent (SIE) is projected to shrink as concentrations of atmospheric greenhouse gases (GHGs) increase, and emperor penguins ( Aptenodytes forsteri ) are extremely sensitive to these changes because they use sea ice as a breeding, foraging and molting h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
237
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(251 citation statements)
references
References 35 publications
(31 reference statements)
5
237
0
Order By: Relevance
“…Recent studies in seabirds have demonstrated how increased variance in survival rates due to environmental variability can drive population declines (Frederiksen et al 2008;Jenouvrier 2009). A hallmark of model predictions for future climate change in the Antarctic includes continued directional change, but also increases in climate variation and extreme events (Solomon et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies in seabirds have demonstrated how increased variance in survival rates due to environmental variability can drive population declines (Frederiksen et al 2008;Jenouvrier 2009). A hallmark of model predictions for future climate change in the Antarctic includes continued directional change, but also increases in climate variation and extreme events (Solomon et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…If such events cause the frequency of years with poor survival rates to increase, accelerated population decline may occur. This prediction can be tested with a demographic model of population dynamics (e.g., Jenouvrier et al 2009) and is the focus of the ongoing research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As climate change is expected to accelerate in the future (IPCC 2014), such explicit links are arguably more relevant in our establishing an ability to predict responses to climate change than broad‐scale phenotypic shifts (e.g., Jenouvrier et al. 2009; Ozgul et al. 2010).…”
Section: Introductionmentioning
confidence: 99%